Human eosinophils express RAGE, produce RAGE ligands, exhibit PKC-delta phosphorylation and enhanced viability in response to the RAGE ligand, S100B - Curran, Colleen S. (Oxford University Press, 2011)
This study tested the hypothesis that human eosinophils produce ligands for the receptor for advanced glycation end-products (RAGE), express RAGE and exhibit RAGE-mediated responses. In examining our microarray data, we identified the presence of RAGE and RAGE ligand (S100A4, S100A6, S100A8, S100A9, S100A11, S100P, HMGB1) transcripts. Expression of eosinophil RAGE mRNA was also compared with a known positive control and further assessed via bioinformatics and sequence analysis of RAGE cDNA. Positive and negative controls were used to identify RAGE, S100A8 and S100A9 protein in human primary eosinophils. Immunoblot assessment of eosinophils treated with cytokines (IL-5 or granulocyte macrophage colony-stimulating factor) indicated an up-regulation of S100A8 and S100A9 production, whereas co-treatment of eosinophils with a RAGE ligand and cytokines displayed a down-regulation in the levels of RAGE. Analysis of eosinophil-conditioned media revealed that eosinophils are capable of releasing RAGE, S100A8 and S100A9. To test the eosinophil response to RAGE activation, the most well-characterized RAGE ligand, S100B, was examined. Treatment of eosinophils with S100B resulted in RAGE-mediated PKC-delta phosphorylation, a 3-fold dose-dependent increase in cell survival and an increase in the level of cellular RAGE. Combined, these studies reveal eosinophil expression of RAGE, RAGE ligands and RAGE-mediated responses. The expression of eosinophil RAGE, soluble RAGE and RAGE ligands may be pivotal to the functions of eosinophils in various human diseases involving RAGE and S100 ligands.